High Performance of Mn2o3 Electrodes for Hydrogen Evolution Using Natural Bischofite Salt from Atacama Desert: A Novel Application for Solar Saline Water Splitting - Jimenez-Arevalo, V; Jimenez-Arevalo, V (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Solar saline water splitting is a promising approach to sustainable hydrogen production, harnessing abundant solar energy and the availability of brine resources, especially in the Atacama Desert. Bischofite salt (MgCl2·6H2O) has garnered significant attention due to its wide range of industrial applications. Efficient hydrogen production in arid or hyper arid locations using bischofite solutions is a novel and revolutionary idea. This work studied the electrochemical performance of Mn2O3 electrodes using a superposition model based on mixed potential theory and evaluated the superficial performance of this electrode in contact with a 0.5 M bischofite salt solution focusing on the hydrogen evolution reaction (HER) and oxygen reduction reaction (ORR) that occur during saline water splitting. The application of the non-linear superposition model provides valuable electrochemical kinetic parameters that complement the understanding of Mn2O3, this being one of the novelties of this work. © 2024 by the authors.